Mobilização juvenil e combate à dengue: Teoria da Mudança, Neuroarquitetura e Nudges - Valeriano, Ana Flávia Aleixo (2024)
The built environment plays a crucial role in combating or increasing the Aedes aegypti epidemic, a vector of diseases such as dengue, the most prevalent urban arbovirus in Brazil. It is estimated that around 85% of this mosquito's breeding sites are located in homes (Ministry of Health of Brazil), due to the practice of accumulating materials and objects in a contaminated form, resulting in places with stagnant water, suitable for the reproduction of the vector. Changing these habits, through simple and effective actions, can be driven by social awareness projects, which prove to be essential tools in this process. Since childhood, educational campaigns in schools, often promoted by public bodies, initiate preventive guidelines. During adolescence, the level of understanding about the severity of the problem increases, allowing a deeper approach. This work proposes an approach based on the "Theory of Change", applied in a case study with young people between 14 and 15 years old, students at a public school in the city of Araxá, Minas Gerais. Furthermore, they are neuroarchitectural analyses, associated with the principles of nudges, to investigate how aspects of the built environment can influence the behavior and practices of individuals in the fight against dengue. Through an innovative pedagogical model, which incorporates dynamic classes, the study seeks to offer practical and impactful experiences, promoting the formation of tension in the fight against Aedes aegypti. The central objective is to promote the empowerment of adolescents in the school environment and hope that these young people, when encouraged to change habits, become agents of transformation within their homes and communities, contributing significantly to the eradication of mosquitoes and the prevention of dengue.